2020
DOI: 10.26656/fr.2017.4(3).380
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of organoleptic, protein, lipid and flavonoid content of commercial starter and isolated culture red dragon fruit peel yogurt

Abstract: Red dragon fruit peel can be processed into yogurt. Yogurt is a coagulated milk product obtained from the lactic acid fermentation-yogurt made from various milk, whether fresh milk, skim milk, or even full cream milk. The additions of red dragon fruit peel may enhance the taste and the therapeutical values. This study was aimed to compare the organoleptic properties, protein, lipid, and flavonoid content of commercial starter and isolated culture red dragon fruit peel yogurt. Red dragon fruit peel yogurt was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Mardiana's research stated that red dragon fruit peel yogurt using Lactobacillus bulgaricus and Streptococcus thermophilus bacterial isolates had higher levels of flavonoids compared to dragon fruit peel yogurt using commercial starters. 12 Flavonoids are known to have antibacterial activity due to their complex formation process with bacterial cell walls. Flavonoids work by damaging bacterial cell membranes in the phospholipid portion to further reduce membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mardiana's research stated that red dragon fruit peel yogurt using Lactobacillus bulgaricus and Streptococcus thermophilus bacterial isolates had higher levels of flavonoids compared to dragon fruit peel yogurt using commercial starters. 12 Flavonoids are known to have antibacterial activity due to their complex formation process with bacterial cell walls. Flavonoids work by damaging bacterial cell membranes in the phospholipid portion to further reduce membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
“…11 Mardiana's research on red dragon fruit peel shows that red dragon fruit peel can be processed into yogurt and has the potential to be a functional food. 12 Yogurt can support human health and survival and improve dysbiosis due to aging. 13 Red dragon fruit added to yogurt with concentrations of 3%, 5%, and 7% showed antimicrobial activity with moderate to high inhibition zones because the growth of E. coli reached the range of 6.06 -15.29 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The chosen dosages were according to a study conducted by Putriningtyas [9] and Mardiana [7]. Red dragon fruit peel yogurt is a fermented product derived from full cream milk, red dragon fruit peel, sucrose and lactic acid bacteria with a ratio of 1: 25%: 10%: 10%.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of action of probiotics includes triggering mucin secretion, immunomodulators in the intestine related to lymphoid tissue and increasing immunosuppressive and decreasing proinflammatory mediators [6]. A study conducted by Mardiana using processed red dragon fruit peel into yogurt showed that the flavonoid content in red dragon fruit peel yogurt could be further developed into a functional drink [7]. Another processed form used in this study is red dragon fruit peel marmalade.…”
Section: Introductionmentioning
confidence: 99%
“…Yogurt diberikan secara oral dengan intubation lambung sekali sehari selama 28 hari. Proses pembuatan yogurt kulit buah naga merah berdasarkan penelitian yang dilakukan oleh Mardiana dan Putriningtyas (Mardiana et al, 2020) (Putriningtyas & Wahyuningsih, 2017) dan Bintari. Pemusnahan tikus dilakukan melalui pembakaran di incinerator.…”
Section: Pendahuluanunclassified